Exploring the Potential of Extracellular Vesicles from Atlantic Cod (Gadus morhua L.) Serum and Mucus for Wound Healing In Vitro - Stefania D’Alessio; Igor Kraev; Bergljót Magnadóttir; Sigrun Lange (Biology)
Novel therapeutic approaches for wound healing have included biomaterials from the Atlantic cod (Gadus morhua L.), with promising results in wound management. The use of extracellular vesicles (EVs), which can be isolated from cod biofluids, remains to be studied. EVs play key roles in cellular communication, and their use both as biomarkers and as therapeutic agents is widely reported in human pathologies, particularly with respect to mesenchymal stem cells. This pilot study characterized the total proteomic cargo content of EVs from cod serum and mucus and assessed the EVs’ potential for regenerative activity in wound-healing processes, using human and mouse fibroblast and keratinocyte in vitro scratch injury models. The pro-regenerative potential of both cod serum EVs and mucus EVs was identified, with differing capacities for accelerating wound closure in fibroblast and keratinocyte cells. This was further supported by varying effects of the cod serum EVs and mucus EVs on cellular vimentin and FGF-2 levels. The serum EV and mucus EV protein cargoes differed with respect to abundance of protein hits and associated enriched functional GO and KEGG pathways, but both were associated with immune, stress and wound-healing processes. Cod EVs may present as innovative therapeutic options for regenerative medicine applications, and our reported findings provide valuable insights for future in-depth studies.